NEW METAPHOR MODELS IN SOCIAL MEDIA DISCOURSE - Orunbayeva Uminiso Sharabidinovna (Bright Mind Publishing, 2025)
This article proposes a practical research approach to investigate emerging metaphor models within social media discourse. The study primarily focuses on social networking platforms widely used by users in Uzbekistan. Drawing on Conceptual Metaphor Theory and comprehensive text analysis, as well as recent research on metaphors in media and social networks, a mixed method is proposed that combines a social media text corpus, semi-automatic metaphor detection, and manual coding. Within this framework, several new metaphor models frequently encountered in daily online communication are examined.
Keywords: metaphor; social media discourse; text corpus; Conceptual Metaphor Theory; mixed methods.